Patients’ Comprehension of Mindfulness-Based Cognitive Behavioral Therapy in an Outpatient Clinic for Resistant Depression: A Cross-Sectional Study - Rodrigues, Michele F.; Campos, Carlos; Pelucio, Luisa; Barreto, Izabel; Machado, Sergio; Appolinario, Jose C.; Nardi, Antonio E.; Levitan, Michelle (Frontiers in Psychology, 2019)
The current study investigated the comprehension of mindfulness-based cognitive behavioral therapy (MBCT) by patients with resistant depression at the Psychiatry Institute of the Federal University of Rio de Janeiro, Brazil. This was the first time the model was used in the institution to treat these patients. In this study, 45 patients were invited to participate in a baseline session of MBCT that consisted in the explanation of the model and experimental exercises conducted by two experienced therapists. Twenty eight patients accepted to participate. At the end of the intervention, the patients completed a self-administered questionnaire designed by our ambulatory to assess their understanding of the method’s goals. Patients with anxiety disorder was also accessed for group comparison. More than 75% of the patients rated the intervention as comprehensible and workable. Compared to patients with depression, patients with anxiety had a better understanding of the mindfulness framework (6.5%) and the meaning of cognitive behavioral therapy (17.6%). Patients that completed the intervention described the baseline session of MBCT as comprehensive and acceptable. These results may allow possible future developments in the practice of mindfulness as a treatment applicable in many condition and settings even in the Brazilian context.